Le déclin du Port de Québec dans la deuxième moitié du XIXe siècle - Camu, Pierre (The Northern Mariner / Le marin du nord, 2010)
Quebec City, the principal Canadian port since the time of the French regime, declined during the last part of the nineteenth century, particularly with respect to Montreal, which was better placed to serve as the maritime gateway to the rapidly developing continental communications of North America. There is some confusion about Quebec’s situation because existing accounts treat in isolation what in fact were two areas of decline : ocean shipping traffic, and the construction of large wooden sailing vessels in the port’s shipyards. The present article addresses both these developments, and also examines efforts by local political and business leaders to improve and modernize the port’s facilities, measures that would contribute to increased traffic in the early part of the twentieth century.